Kolemanit, Üleksit ve Tinkal Takviyeli Polyester Kompozitlerin Termofiziksel Özelliklerinin İncelenmesi - Yanen, Cenk; Dağ, Mustafa; Aydoğmuş, Ercan (Osman SAĞDIÇ, 2022)
Bu araştırmada bor fabrikasından çıkan kolemanit, üleksit ve tinkal cevheri doymamış polyestere takviye edilerek kompozit malzeme elde edilmiştir. Kütlece farklı oranlarda kullanılan bu dolguların polyester kompozitin yoğunluğuna, Shore D sertliğine, ısıl iletkenlik katsayısına ve ısıl kararlılığına etkileri araştırılmıştır. Elde edilen sonuçlara göre karışımdaki bor fabrikası bileşenlerinin kütle oranı yükseldikçe polyester kompozitin yoğunluğu, sertliği, aktivasyon enerjisi ve ısıl iletkenlik katsayısı artmıştır. Kolemanit, polyester kompozitin yoğunluğunu ve Shore D sertliğini diğer dolgu maddelerine göre daha fazla arttırmıştır. Ayrıca tinkal cevheri polyester kompozitin ısıl iletkenlik katsayısını diğerlerine göre en az yükseltmiştir. Ayrıca polyester kompozitin aktivasyon enerjisi değerleri Coats-Redfern yöntemine göre kolemanit, üleksit ve tinkal cevheri olarak büyükten küçüğe doğru sıralanmıştır. Polyester kompozitlerin aktivasyon enerjilerindeki artış, termal kararlılıktaki yükselişin bir göstergesidir

In this research, composite material has been obtained by reinforcing colemanite, ulexite, and tincal ore from the boron factory to unsaturated polyester. The effects of these fillers, which are used in different ratios by mass, on the density, Shore D hardness, thermal conductivity coefficient, and thermal stability of the polyester composite have been investigated. According to the results obtained, as the mass ratio of the boron factory components in the mixture raised, the density, hardness, activation energy, and thermal conductivity coefficient of the polyester composite increased. Colemanite increased the density and Shore D hardness of the polyester composite more than other fillers. Besides, tincal ore raised the thermal conductivity coefficient of the polyester composite the least compared to the others. Also, the activation energy values of the polyester composite were ordered from largest to smallest as colemanite, ulexite, and tincal ore according to Coats-Redfern method. The increase in the activation energies of polyester composites is an indication of the raise in thermal stability
Investigation of Thermophysical Properties of Colemanite, Ulexite, and Tincal Reinforced Polyester Composites
Keywords: Engineering; Mühendislik